Erosion wear characteristics of step-wise layered polymer composite materials by silica sand particles. (December 2022) - Boggarapu, Vasavi; Jain, Satish; Ojha, Shakuntala; Bandaru, Aswani Kumar; Gujjala, Raghavendra
Polymer composite materials (PCMs) can sustain themselves in harsh environments without suffering any loss of properties of the constituents. The present study focussed on erosion wear behavior of step-wise layered polymer composite materials (LPCMs). Samples were fabricated with epoxy as matrix and aluminum as filler particles using hand lay-up technique. Volume fraction of the filler was varied at four different layers along the direction thickness. Experiments were conducted at room temperature using angular shaped silica sand erodent impacting at 151 m/s and at impingement angles of 30°, 45°, 60° and 90°. Due to the variation in filler content, testing of samples was performed at two different orientations: i) top to bottom (T-B) and ii) bottom to top (B-T). The increased filler content reduced the erosion wear as tested from B-T, while a reverse trend was observed along T-B. Moreover, erosion wear was found to be higher at 45° impingement angle indicating the semi-ductile nature of LPCMs. At this angle, the erosion wear rate at top layer was 76.47% lower compared to bottom due to the presence of high filler content.